Hippocampal brain‐derived neurotrophic factor determines recruitment of anatomically connected networks after stress in diabetic mice. Issue 12 (6th November 2018) - Wosiski‐Kuhn, Marlena; Bota, Mihail; Snider, Christina A.; Wilson, Steven P.; Venkataraju, Kannan U.; Osten, Pavel; Stranahan, Alexis M.
Abstract: Diabetes increases adrenal steroids in humans and animal models, but potential interactions with psychological stress remain poorly understood. Diabetic rodents exhibit anxiety and reductions in hippocampal brain‐derived neurotrophic factor (BDNF) expression, and these studies investigated whether loss of BDNF‐driven hippocampal activity promotes anxiety and disinhibits the HPA axis. Mice with genetic obesity and diabetes (db/db) received intrahippocampal injections of lentivirus for BDNF overexpression (db/db‐BDNFOE), and Wt mice received lentiviral constructs for BDNF knockdown (Wt‐BDNFKD). Behavioral anxiety and glucocorticoid responses to acute restraint were compared with mice that received a fluorescent reporter (Wt‐GFP, db/db‐GFP). These experiments revealed that changes in hippocampal BDNF were necessary and sufficient for behavioral anxiety and HPA axis disinhibition. To examine patterns of stress‐induced regional activity, we used algorithmic detection of cFos and automated segmentation of forebrain regions to generate maps of functional covariance, which were subsequently aligned with anatomical connectivity weights from the Brain Architecture Management database. db/db‐GFP mice exhibited reduced activation of the hippocampal ventral subiculum (vSub) and anterior bed nucleus of stria terminalis (aBNST), and increases in the paraventricular hypothalamus (PVH), relative to Wt‐GFP. BDNFKD recapitulated this pattern in Wt mice, and BDNFOE normalized activation of the vSub > aBNST > PVH pathway in db/db mice. Analysis of forebrain activation revealed largely overlapping patterns of network disruption in db/db‐GFP and Wt‐BDNFKD mice, implicating BDNF‐driven hippocampal activity as a determinant of stress vulnerability in both the intact and diabetic brain.